The Form of the Solutions and Periodicity of Some Systems of Difference Equations - M. Mansour; M. M. El-Dessoky; E. M. Elsayed (Discrete Dynamics in Nature and Society)
This paper is devoted to get the form of the solutions and the periodic nature of the following systems of rational difference equations xn+1=xn-5/(-1+xn-5yn-2),  yn+1=yn-5/(±1±yn-5xn-2), where the initial conditions are real numbers.